The first Swedish Read & Publish agreement: An evaluation of the Springer Compact pilot - Olsson, Lisa; Francke, Helena; Lindelöw, Camilla Hertil; Willén, Niklas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
In this paper we summarise the lessons learned from the first Swedish Read & Publish agreement: Springer Compact with Springer Nature (2016-07-01 – 2018-12-31). We set out to put the Swedish agreement in an international context and to examine the effects of the agreement regarding economy, publication outcome, administration and researchers’ attitudes and practices in Sweden. Publication data, economic data, as well as survey data from administrative staff and corresponding authors were collected and analysed. Based on the analyses, the advantages and disadvantages of Read & Publish agreements are discussed. The advantages include increase in OA publishing, improved OA workflows and ease for researchers. The disadvantages include the risk of conserving the current system and its associated high costs.